Job Burnout Is Associated With Prehospital Decision Delay: An Internet-Based Survey in China - Yin, Han; Jiang, Cheng; Shi, Xiaohe; Chen, Yilin; Yu, Xueju; Wang, Yu; Li, Weiya; Ma, Huan; Geng, Qingshan (Frontiers in Psychology, 2022)
Background: Prehospital delay is associated with non-modifiable factors such as age, residential region and disease severity. However, the impact of psychosocial factors especially for job burnout on prehospital decision delay is still little understood. Method: This internet-based survey was conducted between February 14th, 2021 and March 5th, 2021 through Wechat platform and web page. Self-designed questionnaire about expected and actual length of prehospital decision time, as well as Chinese version of Maslach Burnout Inventory-General Survey, Type D Personality Scale-14 and Social Support Rating Scale were applied. 1039 general participants with history of perceptible but tolerable body discomfort were included. Results: The top six reasons for prehospital decision delay were (1) endure until self-healing (50.7%), (2) too busy to ask for leave (40.3%), (3) process for seeing a doctor too complicated (35.8%), (4) too tired after work (26.2%), (5) worry about the expenditure (16.6%) and (6) fear of being identified as with serious problem (14.5%). Univariate analyses revealed that older age (p=0.001), type D personality (p=0.025), job burnout (p=0.055) and worrying about expenditure (p=0.004) were associated with prolonged prehospital decision time, while engaged in medical related job (p=0.028) and with more social support (p=0.066) would shorten the delay. Multivariate analysis using logistic regression model with forward selecting method showed that age (per 10 years, OR 1.19 [1.09-1.31], p<0.001), job burnout (per 10 points in MBI-GS, OR 1.17 [1.04-1.31], p=0.007) and worrying about expenditure (OR 1.75 [1.25-2.47], p=0.001) were the three determinants for prehospital decision delay (>7 days). Mediating effects were analyzed by using bias-corrected percentile Bootstrap methods (N=10000). Social support was found partially mediated the relationship between the determinants and prehospital decision time. The partial mediating effect of social support accounted for 24.0% of the total effect for job burnout, and 11.6% for worrying about expenditure. Conclusion: Psychosocial factors have nonnegligible impact on prehospital decision delay. The crucial part for prehospital decision delay may be the lack of motivation inside. Job burnout and lack of social support, as two commonly-seen features in modern world, should be given enough consideration in disease prevention and treatment.